Sustainable management of the potato cyst nematode, Globodera rostochiensis, with two microbial fermentation products - Pulavarty, Anusha; Singh, Ankit; Smyth, David; Mehta, Jai Prakash; Horgan, Karina; Kakouli-Duarte, Thomais (Frontiers in Plant Science, 2022)
Potato cyst nematodes (PCN) cause an overall 9% yield loss of total potato production worldwide. Research on sustainable management of PCN is still under progress. Two microbial fermentation products (MFPs) from Alltech, a proprietary blend formulated with a bacterial fermentation media and a Cu component (MFP5075), and a microbial based product (MFP3048), were evaluated against the PCN Globodera rostochiensis. In laboratory tests, effectiveness of the MFPs was recorded in terms of PCN juveniles (J2) hatching from cysts, J2 mortality and their attraction towards potato roots using pluronic gel. Greenhouse trials were conducted to study the effect of the products on PCN infestation in potato plants and a pilot scale experiment was conducted to study the impact of these MFPs on nematode biodiversity in garden soil. All treatments were performed within a concentration range of 0, 0.5, 1 and 2% (v/v) MFP5075 and 2, 6, 10 and 20g/10ml (w/v) MFP3048. The attraction assay, juvenile hatching and the PCN infestation in plants results were compared with those in an untreated control and a commercial nematicide (NemguardTM) treatment. After 24 hours of treatment with 0.5% and 1% MFP5075, a 13-fold and 43-fold reduction, respectively relative to J2 survival was recorded compared to that of untreated control. However, no J2 survived at 2% and above concentration of the MFP5075 treatment. In the attraction assay, a 20-fold and 8-fold reduction in number of J2 attracted towards potato roots was observed, when treated with MFP5075, compared to the untreated and the NemguardTM treatment, respectively. No J2 hatched in the MFP5075 treatment, whereas mean numbers (±SE) of 24311.5, 302.5 and 1.30.6 J2 were noted in the untreated control, MFP3048 and the NemguardTM treatment, respectively. The treatment with the MFPs compromised the integrity of the unhatched J2, whereas the internal organs of the unhatched J2 could be clearly identified in the untreated control. In plant infestation studies treatment with MFP3048 and MFP5075 caused 90.6 and 84.9 percent reduction in PCN infestation respectively in terms of cysts developed on roots compared to untreated control. Overall, results indicate that MFPs could potentially provide a promising alternative for sustainable PCN management.